PERAN PENYULUH PENDAMPING TERHADAP EFEKTIVITAS KINERJA BRIGADE PANGAN DI PROVINSI LAMPUNG - Septiana Septiana; Danny Alfandy (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Food security is a key pillar of national agricultural development. Although the Indonesian government has established the Food Brigade (Brigade Pangan/BP) as a strategy to accelerate food self-sufficiency through technology-based agricultural modernization, empirical evidence regarding the influence of agricultural extension officers on the effectiveness of Food Brigade performance remains limited. This study aimed to analyze the role of agricultural extension facilitators in improving the effectiveness of Food Brigade performance in Lampung Province. A quantitative survey with a correlational design was employed. The respondents consisted of 38 Food Brigade extension facilitators in 2024 from four regencies in Lampung Province: Tulang Bawang, East Lampung, Central Lampung, and Mesuji. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and Spearman's Rank Correlation using SPSS version 24.0. The findings revealed a strong and statistically significant positive relationship between the role of agricultural extension officers and the effectiveness of Food Brigade performance (r = 0.647; p < 0.05). The results indicate that the more effectively extension officers perform their roles as facilitators, motivators, educators, and innovators, the higher the effectiveness of Food Brigade performance. These findings provide empirical evidence that strengthening the capacity of agricultural extension facilitators is a strategic factor in enhancing Food Brigade performance and offers practical input for improving Food Brigade institutional development and agricultural extension policies to support the achievement of national food self-sufficiency. ABSTRAK Ketahanan pangan merupakan pilar utama pembangunan pertanian nasional. Meskipun Brigade Pangan (BP) telah dibentuk sebagai strategi percepatan swasembada pangan melalui modernisasi pertanian berbasis teknologi, bukti empiris mengenai pengaruh peran penyuluh pendamping terhadap efektivitas kinerja Brigade Pangan masih terbatas. Penelitian ini bertujuan menganalisis peran Penyuluh Pendamping terhadap efektivitas kinerja Brigade Pangan di Provinsi Lampung. Penelitian menggunakan desain survei kuantitatif dengan pendekatan korelasional. Responden berjumlah 38 Penyuluh Pendamping Brigade Pangan Tahun 2024 yang tersebar di Kabupaten Tulang Bawang, Lampung Timur, Lampung Tengah, dan Mesuji. Data dikumpulkan menggunakan kuesioner skala Likert dan dianalisis secara deskriptif kuantitatif serta uji korelasi Rank Spearman menggunakan SPSS 24.0. Hasil penelitian menunjukkan terdapat hubungan positif yang kuat dan signifikan antara peran penyuluh pertanian dan efektivitas kinerja Brigade Pangan (r = 0,647; p < 0,05). Temuan ini menunjukkan bahwa semakin optimal peran penyuluh sebagai fasilitator, motivator, edukator, dan inovator, semakin tinggi efektivitas kinerja Brigade Pangan. Hasil penelitian memberikan bukti empiris bahwa penguatan kapasitas penyuluh pendamping merupakan faktor strategis dalam meningkatkan kinerja Brigade Pangan serta menjadi dasar bagi pengembangan kelembagaan Brigade Pangan dan kebijakan penyuluhan pertanian untuk mendukung pencapaian swasembada pangan.